Religious ceremonies and the ethical development of medical sciences students: A qualitative study on participation barriers and perceived value - Amir Hossin Moradpour Dehnavi; Abolfazl Alavi; Amin Beigzadeh; Ali Reza Yusefi (PLoS ONE, 2026)
Religious ceremonies can play a pivotal role in shaping ethical values among medical sciences students. However, participation in such ceremonies is often influenced by multiple academic, social, and cultural factors. This study aimed to explore the perceived value of religious ceremonies and the barriers affecting student participation in these practices within the context of their ethical development. This qualitative study was conducted at Sirjan School of Medical Sciences in southern Iran from March to July 2025, using a latent content analysis approach grounded in the interpretivist paradigm. Semi-structured, in-depth interviews were conducted with 33 students from diverse academic programs and backgrounds. Data were analyzed inductively based on Graneheim and Lundman’s framework using MAXQDA 2022 software. Trustworthiness was ensured through Lincoln and Guba’s criteria including credibility, confirmability, dependability, and transferability. Seven main themes and twenty- four subthemes emerged. The themes included: (1) Time and Academic Pressure (e.g., course overload, exam clashes); (2) Perceived Irrelevance (e.g., disconnection from professional goals); (3) Cultural and Personal Beliefs (e.g., secular upbringing, concerns about religious imposition); (4) Social Dynamics (e.g., fear of judgment, peer influence); (5) Institutional Support (e.g., lack of promotion, insufficient facilities); (6) Perceived Ethical Value (e.g., development of professionalism and compassion); and (7) Emotional and Community Benefits (e.g., stress relief, sense of belonging, spiritual recharge). While religious ceremonies hold perceived ethical and emotional value for many students, numerous academic, institutional, and cultural barriers limit participation. Integrating religious practices into educational contexts in a more inclusive, flexible, and voluntary manner could enhance students’ moral development without alienating diverse beliefs.